Innovations in Technologies for Fermented Food and Beverage Industries - Panda, Sandeep Kumar; Shetty, Prathapkumar Halady; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book covers innovations in starter culture, production of health beneficial fermented food products, technological intervention in beer, wine and spirits production, marketing of alcoholic beverages, modernization of dairy plants for production of fermented dairy products, non-diary probiotics, development of automatic fermenters, and packaging technology. Furthermore, it includes genetic engineering for improved production and quality improvement of food and beverages, which allows forecasting of the quality of the final product. Specifically this includes applications of hybrid methods combining multivariate statistics and computational intelligence, the role of consumers in innovation of novel food and beverages, and IPRS in respect to food and beverages. Innovations in Technologies for Fermented Food and Beverage Industries is a resource for students, researchers, professionals in the industry, as well as governments in theirefforts to adopt technologies of their interest.
1 Innovative technologies and implications in food and beverage industries: an overview -- 2 Yeasts and Lactic acid bacteria as potential starter cultures for fermented foods -- 3 Advances in fermentation technology for health -- 4 Advances in fermentation technology for novel food products -- 5 Beer, Wine and Spirits : Technological interventions that benefit production, quality and economics -- 6 Alcoholic beverages: Technology for next generation marketing -- 7 Advances in probiotics, prebiotics and nutraceuticals -- 8 Probiotic milk products: Inventions towards ultramodern production plants -- 9 Non-dairy probiotic foods: Innovations and current market status -- 10 Technological Interventions in Fermented Meat Production: the Commercial Perspective -- 11 Modernisation of fermenters for large scale production in food and beverage industry -- 12 Advances in genetic engineering for higher production and quality improvement of food and beverages -- 13 Innovative and safe packaging technologies for food and beverages: updated review -- 14 Role of consumers in innovation of novel food and beverages -- 15 IPRS in respect to food and beverages -- 16 Application of computational intelligence techniques for forecasting problematic wine fermentations using data from classical chemical measurements.
Keywords: Food -- Microbiology; Food science; Food Microbiology; Food Science